Pengaruh Motivasi Belajar dan Kompetensi Berbasis E-Learning di Masa Pendemi Covid-19 - Yanita Ella Nilla Chandra; Syamsurizal Syamsurizal; Rizka Sakinah (Telaah Bisnis, 2021)
This study aims to identify learning motivation and competency development based on e-development through e-learning for students to meet the needs of the work industry. This research uses a quantitative approach with explanatory research methods. The Department of Business Administration, State Polytechnic of Jakarta conducted this research. In this research, the population was 1,094 students of the Department of Business Administration, State Polytechnic of Jakarta. The sample used in this study was 100 taken by random sampling. The data collected in this study used a closed questionnaire with a Likert scale of 5. The data analysis carried out in this study was a multiple linear regression analysis. The research results explain that learning motivation influences the competence of lecturers and e-learning methods given to students. The research results also clarify that the competencies possessed in the online learning on the e-learning have a positive and significant effect through the e-learning method taught by lecturers.